2006
DOI: 10.21273/horttech.16.2.0225
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control Efficacy of Organic Mulches in Two Organically Managed Bell Pepper Production Systems

Abstract: A 2-year field study in Lexington, Ky., evaluated weed control efficacy and influence on yields of several organic mulches in two organically managed bell pepper (Capsicum annuum) production systems. Five weed control treatments [straw, compost, wood chips, undersown white dutch clover (Trifolium repens) “living mulch,” and the organically approved herbicide corn gluten] were applied to two production systems consisting of peppers planted in double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 17 publications
1
28
1
Order By: Relevance
“…In our experiment, weed mass, or weed mass expressed in the time needed for weeding, was significantly reduced by mulching, and, unlike Law et al (2006) [29], who found that one mulching at the beginning of the season was not sufficiently able to control weeds throughout the season, we experienced a different tendency: less and less time was needed for weeding as the season progressed. In one of our earlier studies [30], a thick layer of straw provided suitable suppression against weeds, but the thickness of mulch (and year, and time of season) were important factors to determine the efficiency of mulching.…”
Section: Discussioncontrasting
confidence: 72%
“…In our experiment, weed mass, or weed mass expressed in the time needed for weeding, was significantly reduced by mulching, and, unlike Law et al (2006) [29], who found that one mulching at the beginning of the season was not sufficiently able to control weeds throughout the season, we experienced a different tendency: less and less time was needed for weeding as the season progressed. In one of our earlier studies [30], a thick layer of straw provided suitable suppression against weeds, but the thickness of mulch (and year, and time of season) were important factors to determine the efficiency of mulching.…”
Section: Discussioncontrasting
confidence: 72%
“…The straw mulch was needed for supplemental weed control in 2003 despite a %153% increase in hairy vetch/rye biomass from 2002 to 2003. For complete weed management, additional hand weeding may also be required in straw mulch systems (Law et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that mulching several weeks after transplanting bell pepper (Capsicum annuum) can improve weed suppression mainly by improving mulch persistence later into the growing season (Law et al, 2006), but mulch application should be done with care to prevent lodging of the crop (Boyhan et al, 2006) and shading of prostrate crop growth (Pedreros et al, 2008). Inhibition of light transmittance appears to be the greatest factor for weed suppression by mulches (Steinmaus et al, 2008).…”
Section: Introductionmentioning
confidence: 99%